The cost‐effectiveness of dapagliflozin versus sulfonylurea as an add‐on to metformin in the treatment of Type 2 diabetes mellitus. Issue 7 (30th April 2015) - Charokopou, M.; McEwan, P.; Lister, S.; Callan, L.; Bergenheim, K.; Tolley, K.; Postema, R.; Townsend, R.; Roudaut, M.
Abstract Aims To assess the cost‐effectiveness of dapagliflozin, a sodium–glucose co‐transporter–2 (SGLT–2) inhibitor, compared with a sulfonylurea, when added to metformin for treatment of UK people with Type 2 diabetes mellitus inadequately controlled on metformin alone. Methods Clinical inputs sourced from a head‐to‐head randomized controlled trial (RCT) informed the Cardiff diabetes decision model. Risk equations developed from the United Kingdom Prospective Diabetes Study (UKPDS) were used in conjunction with the clinical inputs to predict disease progression and the incidence of micro‐ and macrovascular complications over a lifetime horizon. Cost and utility data were generated to present the incremental cost‐effectiveness ratio (ICER) for both treatment arms, and sensitivity and scenario analyses were conducted to assess the impact of uncertainty on the final model results. Results The dapagliflozin treatment arm was associated with a mean incremental benefit of 0.467 quality‐adjusted life years (QALYs) [95% confidence interval (CI): 0.420; 0.665], with an incremental cost of £1246 (95% CI: £613; £1637). This resulted in an ICER point estimate of £2671 per QALY gained. Incremental costs were shown to be insensitive to parameter variation, with only treatment‐related weight change having a significant impact on the incremental QALYs. Probabilistic sensitivity analysis determined that dapagliflozin had a 100% probability of being cost‐effective at a willingness‐to‐pay threshold of £20 000 per QALY. Conclusions Dapagliflozin in combination with metformin was shown to be a cost‐effective treatment option compared with sulfonylurea from a UK healthcare perspective for people with Type 2 diabetes mellitus who are inadequately controlled on metformin monotherapy.